Ռազմական ուսումնական հաստատություններում ապագա հրամանատարների առաջնորդության որակների ձևավորումը - Մանուկյան, Հարություն («Ալվարդ Օհանջանյան Վառլենի»)
This study examines the development of leadership qualities in future commanders within the Republic of Armenia’s military educational institutions. Attention is primarily given to modern theories of leadership, as practical methods for contributing to students’ leadership development are discussed in relation to their applicability in the military educational field. Leadership teaching methodologies are analysed, focusing on teamwork, decision-making, self-confidence, responsibility, and student communication skills. Consideration is also given to the effectiveness of leadership development programs and exercises used in the military educational institutions. Additional attention is given to military psychological and organisational aspects of leadership education, which are most applicable for the formation of future commanders. Работа посвящена изучению процесса формирования лидерских качеств будущих командиров в военно-учебных заведениях Республики Армения. Были изучены современные теории лидерства, их возможные применения в сфере военного образования, а также практические методы, способствующие развитию лидерских качеств у студентов. Отдельное внимание уделялось образовательным методикам, нацеленным на развитие процесса командной работы, принятия решений, а также повышение чувств личной уверенности, ответственности и коммуникативных навыков. Был проведен анализ эффективности программ и упражнений усовершенствования лидерских качеств будущих командиров. Также уделялось внимание аспектам военной психологии и организационным особенностям, влияющим на общее формирование лидерских качеств будущих командиров. Աշխատանքը նվիրված է ՀՀ ռազմաուսումնական հաստատություններում ապագա հրամանատարների առաջնորդական որակների ձևավորման գործընթացի ուսումնասիրությանը։ Ուսումնասիրվում են առաջնորդության ժամանակակից տեսությունները, դրանց կիրառելիությունը ռազմական կրթության ոլորտում, ինչպես նաև` գործնական մեթոդները, որոնք նպաստում են ուսանողների մեջ առաջնորդական հմտությունների զարգացմանը։
Keywords: Հոգեբանություն